2015
DOI: 10.1016/j.econlet.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Patience and long-run growth

Abstract: Complementing research on the effect of patience on individual behavior, we present empirical evidence that patience is an important determinant of long-run income differences between countries. To account for a potential endogeneity bias, we instrument patience by information on how languages spoken in the countries of our sample require speakers to encode time. The economic impact of patience and growth is sizable. Our results suggest that increasing patience by one standard deviation raises per-capita incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 16 publications
2
20
0
1
Order By: Relevance
“…poor). This result is consistent with the recent finding of Hübner and Vannoorenberghe () whereby increasing patience by one standard deviation raises per‐capita income by between 34 and 78 percent.…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…poor). This result is consistent with the recent finding of Hübner and Vannoorenberghe () whereby increasing patience by one standard deviation raises per‐capita income by between 34 and 78 percent.…”
Section: Introductionsupporting
confidence: 93%
“…Consequently, households with a lower time preference eventually own more capital, compared to those households with a higher time preference. Recently, Hübner and Vannoorenberghe (2015) have shown that increasing patience by one standard deviation raises per capita income by between 34 and 78 percent. Given that leisure is a normal good, this also implies that households with a lower time preference not only own more wealth but also enjoy more leisure.…”
Section: Proposition 2 (Time Preference and Distribution)mentioning
confidence: 99%
“…Some studies focus on future‐time reference which is argued to have an effect on speaker's intertemporal choices, on long‐term orientation, on economic performance and on corporate decisions. For instance, Hubner and Vannoorenberghe (2015a) explore whether patience, proxied by measures of time discounting and long‐term orientation, is a determinant of economic outcomes. Using weak FTR as an instrument, the authors provide evidence for a positive association between patience and output per worker, total factor productivity, innovation and capital stock.…”
Section: Literaturementioning
confidence: 99%
“…Individu yang mempunyai sabar sama halnya mereka mampu mengendalikan diri mereka terutama dalam keadaan yang tidak stabil (Alan & Ertac, 2015). Selain dari pada itu sikap ini juga mampu meningkatkan potensi usia hidup pada individu karena berkaitan dengan sistem dalam tubuh yang teratur dan cenderung membuat organ-organ menjadi terkendali (Hübner & Vannoorenberghe, 2015).…”
Section: Coping Strategy Metode Campuran Kesabaranunclassified